School Supervisors Facilitation Skills In Junior High Schools - Najoan, Yunita A.; Lengkong, Jeffry S. J.; Mongdong, Romi J. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to describe the facilitation skills, enabling and hindering factors of school supervisors' facilitation skills in Amurang State Junior High School. The study used a qualitative approach and a case study method. The location of the study was Amurang Public Junior High School in South Minahsa County. The research data sources were school superintendents, principals, classroom trustees, and subject teachers. The data collection techniques used were interviews, observations, and documentation studies. The data analysis technique used refers to the interaction model. The results of the study showed that facilitation skills by the superintendent included listening to each principal's needs, conducting a needs analysis for school program development, posing cultivating questions, building consensus or agreement, and setting meeting times; factors supporting facilitation skills were categorized as school superintendent internal and external factors; and hindering factors of facilitating skills were categorized as superintendents' personal factors and principals' personal factors. Then, in addition to conducting a discussion of the research results related to their relevance to theory and previous research, it also puts forward research conclusions and suggestions related to the urgency of facilitation skills regarding the school acquisition process.